Strategi Perpustakaan Dalam Meningkatkan Minat Baca Mahasiswa Universitas Islam Negeri Bandung - Rafii Athallah Aqsal; Sahra Fajrin Dytiar (UIN Sunan Gunung Djati Bandung, 2023)
Universities need to have various facilities to support the success of university program goals, one of the facilities that support the success of a university plan is the provision of a library that also performs tridharma by providing, organizing, and providing services to library users, the UIN Sunan Gunung Djati Bandung library was previously quite ineffective because it took a long time to receive the right literature from now on it has changed by adopting library digitization to make the right literature easily available, the purpose of this article is to discuss the strategy of the UIN Bandung library in increasing student interest in reading, This research was conducted by applying qualitative methods, the post-positivistic research paradigm is also included in descriptive qualitative research, the informants were selected by researchers using purposive sampling techniques, the strategy of the UIN Sunan Gunung Djati Bandung library in increasing reading interest has supporting factors and inhibiting factors, the need to implement library strategies by holding library planning in determining the goals to be set, providing services such as distributing information and utilizing resources and facilities, and providing facilities to support excellent library services and achieve vision so that in increasing student interest in reading can meet the targets to be achieved